Fibrodysplasie ossifiante progressive (FOP) à propos d’un cas - BADJI Nfally; Coumba K DIENG; Papa Malick DIOUF (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2025)
Fibrodysplasia ossificans progressiva (FOP) or myositis ossificans is an extremely rare progressive genetic disease that affects one in a million people. The mode of transmission of FOP is autosomal dominant, with no association with race, sex or geographic distribution. We report a case of fibrodysplasia ossificans progressiva (FOP) or myositis ossificans in a 5-year-old patient admitted for suspected multiple exostoses disease. The clinical examination revealed limited joint mobility of the spine, shoulders, elbows and a skeletal deformation in the craniocaudal and proximo-distal directions. The diagnosis of FOP had been suggested by the typical appearances on standard skeletal radiography. The patient had received treatment with corticosteroids and anti-inflammatories. The course was punctuated by episodes of flare-ups and remissions followed by death in a picture of cardio-respiratory distress.